Cold induced vasodilation - Daanen, Hein (Henry Stewart Talks, 2012)
History of Cold Induced Vasodilation (CIVD), CIVD mechanisms, Reproducibility of CIVD, Factors affecting CIVD, CIVD and risk for cold injuries, CIVD and manual dexterity, CIVD training, Conclusions and recommendations for future research